Diverging trajectory patterns of systemic versus vascular inflammation over age in healthy Caucasians and African-Americans. Issue 2 (April 2015) - Enkhmaa, Byambaa; Anuurad, Erdembileg; Zhang, Wei; Kim, Kyoungmi; Berglund, Lars
Abstract Objective Age and inflammation are risk factors for cardiovascular disease but the impact of inflammation on cardiovascular risk across the lifespan is not understood. We investigated whether an inflammatory burden is modulated by age in healthy subjects. Methods Caucasian and African-American families were recruited from the general population (age range: 6–74 years, n = 267). Systemic inflammation was assessed by C-reactive protein (CRP), serum amyloid A (SAA), fibrinogen, haptoglobin and α-acid glycoprotein, and vascular inflammation was assessed by pentraxin-3 (PTX-3), soluble intercellular adhesion molecule-1 (sICAM-1) and soluble vascular cell adhesion molecule-1 (sVCAM). To collectively assess systemic or vascular factors across the age spectrum, a composite z-score for each marker category was calculated. Results There was a contrasting pattern in systemic versus vascular inflammatory burden over age with an increase in systemic but a decrease in vascular markers in both ethnic groups. The results remained unchanged after adjustments for the covariates and covariance. When looking at individual markers to examine which markers are most contributing factors to the composite scores, CRP and SAA were significantly and positively associated with age, while PTX-3 and sVCAM were significantly and negatively associated with age in both ethnic groups. Conclusions The composite z-score for systemic inflammation increased with age, while the composite z-score for vascular inflammation declined with age, irrespective of ethnicity. The findings illustrate a regulatory relationship between age and inflammation, and suggest that a perceived elevation of vascular markers among the very young may be an indication of physiological changes rather than reflecting a disease process.